Data for "Embedding Regional Organisations in Strategic Culture: Russian Strategic Thought and the Commonwealth of Independent States" - Murad Nasibov; Andrea Gawrich; Justus Liebig University Giessen (My University, 2025)
This dataset comprises a curated list of Russian-language peer-reviewed journal articles on the Commonwealth of Independent States (CIS), compiled by Murad Nasibov as of 18 February 2022. It serves as an appendix to the publication and is made publicly available as supplementary data. Source and Collection Method The articles were sourced from eLIBRARY.ru, the largest academic publication repository in the Russian Federation, which also indexes scholarly output from across the post-Soviet space. Two search terms were used in Cyrillic: “Содружество Независимых Государств” (Commonwealth of Independent States) and “СНГ” (CIS). The search was restricted to peer-reviewed journal articles in political science. Out of 424 initial search results: • 319 articles were accessible in full text, • 44 were excluded (due to duplication, wrong language, irrelevance, or technical issues), • Resulting in a final, curated corpus of 275 full-text articles. No systematic bias was identified among the inaccessible articles, ensuring a high degree of representativeness for the scholarly discourse on the CIS in the Russian-speaking academic community. Linguistic and Geographic Composition • 75% of authors are affiliated with Russian institutions, • Of those, 31% of the total have Moscow-based institutional affiliations, • 25% of authors are affiliated with institutions in other CIS countries. • The corpus includes contributions from scholars associated with state-linked institutions and 33 dual-role individuals who simultaneously held academic and governmental or CIS-related bureaucratic positions. Temporal Coverage and Scope The dataset covers publications from 2002 to 2021, with the majority of the articles published after 2008. Format and Accessibility Due to copyright restrictions, the full texts of the articles cannot be provided. Instead, the dataset includes a reference list in the formats .csv and .xlsx, containing metadata and hyperlinks to the articles hosted on eLIBRARY.ru. This allows users to recreate the full-text collection themselves using a script and the provided links under the "Hyperlink" column. Additionally, a .pdf version of the list is included for convenience and readability.
Keywords: Commonwealth of Independent States; Epistemic community; Strategic Culture; Eurasian regionalism; Post-Soviet; Regional Organisations; Reflexive Thematic Analysis; ddc:320